1988
DOI: 10.1002/jca.2920040403
|View full text |Cite
|
Sign up to set email alerts
|

Plateletpheresis concentrates produced in 30 minutes along with plasma and packed red cells: Preliminary results

Abstract: Centrifugal devices for donor plasmapheresis that collect platelets as a by-product have recently been introduced. The platelet yield ranges from 1.2 to 2 X 10(11) per collection, and the collection time exceeds 50 minutes. An attempt to increase yields and to reduce the procedure time was carried out at our center, taking advantage of the Dideco Eccentriplate (Dideco spa, Mirandola, Italy). Within 30 minutes, 510 ml of plasma were collected along with 3.3 X 10(11) platelets. The shift of donors from whole blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This concept of multicomponent donation has expanded from the field of autologous to the field of homologous donations. In the late 80s, Valbonesi et al reported on the concurrent collection of PLT concentrates in 30 min along with plasma and RBCs in allogeneic donors [10]. A technique was developed that allowed the collection of 3AE68 · 10 11 PLTs, 250 ml of plasma, and 225 ml RBCs with an Hct of 66AE5%.…”
Section: Introductionmentioning
confidence: 99%
“…This concept of multicomponent donation has expanded from the field of autologous to the field of homologous donations. In the late 80s, Valbonesi et al reported on the concurrent collection of PLT concentrates in 30 min along with plasma and RBCs in allogeneic donors [10]. A technique was developed that allowed the collection of 3AE68 · 10 11 PLTs, 250 ml of plasma, and 225 ml RBCs with an Hct of 66AE5%.…”
Section: Introductionmentioning
confidence: 99%
“…Since we had difficulty attaining such results routinely in our hemapheresis unit, we decided to modify the standard Fresenius procedure in order to reduce the needleto-needle time to less than 60 min and to collect more than 4 X 10" platelets, as we normally do with other blood cell separators [4,5,6]. A study was started with 45 donors enrolled in accordance with the Italian regulations for blood donation [7].…”
Section: Introductionmentioning
confidence: 99%